Obesity among peruvian children under five years of age in 2017: A geographic information system analysis - Sotomayor Beltran, Carlos (2018)
Introduction: The Sustainable Development Goal (SDG) number 2 aims to end malnutrition in all its forms. To reach this goal one of the several health problems to tackle is childhood obesity. Aim: In this study, spatial data for the prevalence of obesity among Peruvian children under five years of age in 2017 is presented and analyzed in order to observe in which regions this disease is a high risk. Material and Methods: By geo-referencing public data provided by the National Institute of Health from Peru and using a Geographic Information System (GIS) tool, it was possible to generate maps of prevalences and also of clusters and outliers at a regional and district level, respectively. Results: Observing at the map of prevalences, it could be identified that in the natural region of the coast there are the highest prevalences of obesity among children under five. A second map showing the hot spots and the outliers is also presented. This second map is very revealing because it shows the districts which are classified as outliers and thus in danger of becoming hot spots for childhood obesity in the future if no action is taken. Conclusion: In view of the spatial distribution of hot spots and outliers of obesity among children under five years of age, it is recommended that health governmental and non-governmental entities from Peru allocate their resources where is urgently needed in order to attempt to reduce childhood obesity, and helping in reaching as well SDG 2.